Adapting the HSE-MS Indicator Tool for Academia: A Psychometric Evaluation of the Academic Teacher Stress Indicator Tool in Italian - Marcatto, Francesco; Ferrante, Donatella; Di Blas, Lisa; Larese Filon, Francesca (La Medicina del Lavoro, 2024)
Background: The assessment of work-related stress is mandatory in Italy, according to Legislative Decree 81/2008. The Academic Teacher Stress Indicator Tool (ATS-IT) was developed to address stress in academic teaching staff by adapting the Health and Safety Executive Management Standards Indicator Tool (HSE-MS IT). Methods: An online ATS-IT survey was administered to all teaching staff at the University of Trieste, yielding 334 valid responses. The survey also included a measure of psychosomatic complaints and demographic questions. Confirmatory factor analysis (CFA) was performed to test the six-factor structure, and reliability was assessed using Cronbach’s alpha.Results: CFA confirmed an excellent fit for the six-factor structure (CFI = .99; TLI = .99; RMSEA = .034). Reliability analysis mainly showed acceptable values (Cronbach’s α ranging from .66 to .91). Significant gender differences were found in the Demands and Control scales, with additional differences based on age and academic role across multiple scales. The ATIS-IT scales were significantly intercorrelated and negatively correlated with psychosomatic complaints. Conclusions: The ATS-IT demonstrates good potential as a valid and reliable instrument for assessing work-related stress among Italian academic teaching staff. Its use can facilitate better stress management and intervention strategies in educational institutions.